Sistem Diagnosis Penyakit Sapi Menggunakan Metode Neighbor Weighted K-Nearest Neighbor Berbasis Android - Idham Triatmaja; Nurul Hidayat; Moch Cholil Mahfud (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Problems in raising cattle is infection of disease. Infection of diseases that arise in each cow can be different so that required accuracy in making the diagnosis (Pambudi, 2010). Cattle ranchers are sometimes difficult to know cow disease due to the limited knowledge of breeders of cattle disease. The difficulty of seeking medical personnel such as veterinarians becomes a problem for farmers because they can not quickly handle cows affected by the disease. When cattle are infected with disease, experts / experts such as veterinarians are very necessary in overcoming it. Based on the explanation of the problem it will be designed an system by combining the object of cow disease research and the NWK-NN method. The title of the study was